2022
DOI: 10.2147/jmdh.s379782
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Home Health Care Service: Data from Saudi Arabia

Abstract: Objective This study aimed to 1) report the prevalence of chronic conditions among Saudi people receiving long-term home health care (HHC) services, 2) identify the predictors of mortality among individuals receiving long-term HHC services, and 3) study the association between frailty and poor health outcomes among HHC users. Design Retrospective cross-sectional descriptive study. Setting and Participants A total of 555 participants were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Conclusively, PIM was associated with frail older adults with polypharmacy and multiple comorbidities. Alkeridy et al [ 57 ] reported the linkage of frailty with poor health outcomes among home health care service (HHCS) users. This retrospective study concluded that frailty serves as a powerful predictor of mortality for a population receiving HHCS.…”
Section: Research On Frailty In Ksa Until Present Daymentioning
confidence: 99%
“…Conclusively, PIM was associated with frail older adults with polypharmacy and multiple comorbidities. Alkeridy et al [ 57 ] reported the linkage of frailty with poor health outcomes among home health care service (HHCS) users. This retrospective study concluded that frailty serves as a powerful predictor of mortality for a population receiving HHCS.…”
Section: Research On Frailty In Ksa Until Present Daymentioning
confidence: 99%